Livedoid vasculopathy as a marker of systemic disease: report of two cases - Raquel Sucupira Andrade Lima; Gustavo Ávila Maquiné; Carolina Talhari; Isabel Cristina Lima Encarnação; Antônio Pedro Mendes Schettini; Mônica Santos (Sociedade Brasileira de Dermatologia, 2014)
The livedoid vasculopathy is an obstructive vascular process of etiology not yet fully known, being possibly associated with several prothrombotic events. It is clinically characterized by the presence of painful and recurring purpuric lesions, which usually suffer ulceration and evolve with formation of white atrophic scars usually located in the lower limbs. Two cases are here reported of painful ulcerated lesions on the lower limbs, in which the identification of VL enabled the diagnosis of systemic diseases.